2020
DOI: 10.1007/s10552-020-01330-z
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent dairy product and calcium intake in relation to later prostate cancer risk and mortality in the NIH-AARP Diet and Health Study

Abstract: Purpose-Although a growing body of evidence supports an early-life contribution to prostate cancer (PCa) development, few studies have investigated early-life diet, and only three have examined early-life dairy product intake, a promising candidate risk factor because of its known/ suspected influence on insulin-like growth factor levels and height.Methods-We used recalled dietary data from 162,816 participants in the NIH-AARP Diet and Health Study to investigate associations for milk, cheese, ice cream, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…intakes of cheese and ice cream, two food items correlated with adolescent red meat intake, and PCa risk [37], as well as inverse findings for adolescent red meat intake and postmenopausal breast cancer risk in the AARP Study (unpublished data). Compared to the previous literature, our analysis brings several methodologic strengths to the study of adolescent diet and PCa.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…intakes of cheese and ice cream, two food items correlated with adolescent red meat intake, and PCa risk [37], as well as inverse findings for adolescent red meat intake and postmenopausal breast cancer risk in the AARP Study (unpublished data). Compared to the previous literature, our analysis brings several methodologic strengths to the study of adolescent diet and PCa.…”
Section: Discussionmentioning
confidence: 86%
“…To inform the possible role of adolescent diet in prostate carcinogenesis, we previously took advantage of data collected in the large, ongoing NIH-AARP Diet and Health (AARP) Study to investigate recalled adolescent dairy product and calcium intake in relation to subsequent PCa risk and mortality [37]. In that study, we observed positive associations for adolescent dairy product and calcium intake, but these associations attenuated after controlling for red meat intake, suggesting that adolescent red meat intake might be related to PCa risk or mortality.…”
mentioning
confidence: 99%
“…A total of four studies were included in this meta-analysis [ 2 , 13 , 14 , 15 ]. The summary RR of prostate cancer for the highest vs. lowest milk intake in childhood and adolescence was 0.98 (95% CI = 0.72–1.32), with moderate heterogeneity (I 2 = 51%) ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…To identify additional papers, the reference lists of selected articles and previous systematic reviews were reviewed. After a series of screening, a total of 15 studies (9 studies for breast cancer, 3 studies for prostate cancer, 2 studies for colorectal cancer, 1 study for breast, prostate, and colorectal cancer) were eligible for this meta-analysis [ 2 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. This study selection process is summarized in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation